Analysis of medical services provided to patients with ankle sprains in Korea between 2015 and 2017: a cross-sectional study of the health insurance review and assessment service national patient sample database. Issue 9 (24th September 2020) - Ryu, Ho-sun; Jung, Boyoung; Yeo, Jiyoon; Kim, Jae-Hong; Nam, Dongwoo; Ha, In-Hyuk
Abstract : Objectives: To provide useful information for policy-makers and clinicians by analysing the medical service use—divided into Western medicine (WM) and Korean medicine (KM)—of patients with ankle sprains in South Korea between 2015 and 2017. Design: Cross-sectional, retrospective, observational study. Setting: Tertiary hospitals, WM hospitals, WM clinics, KM hospitals, KM clinics and others in South Korea. Participants: We analysed claim data and patient information from the 2015 to 2017 Health Insurance Review and Assessment National Patient Sample (HIRA-NPS) dataset, including 151 415 patients diagnosed with a 'dislocation, sprain and strain of joints and ligaments at ankle and foot level' (10th revision of the International Statistical Classification of Diseases code S93) who used medical services at least once in 3 years between January 2015 and December 2017 in South Korea. Primary and secondary outcome measures: Cost of medical care, number of consultations, type of institution visited, types of treatment. Results: There were 160 200 consultations and 53 044 patients in 2015, 149 956 consultations and 50 830 patients in 2016 and 140 651 consultations and 47 541 patients in 2017. The total treatment costs were US$3 355 044.21, US$3 245 827.70 and US$3 128 938.46 in 2015, 2016 and 2017, respectively. The most common age was 10–19 years. The most frequent type of visit was KM outpatient visit (56%). Physiotherapy was most common in WM outpatient visits, while acupuncture was most common in KM visits. Most patients used one institution, rather than alternating between WM and KM. Conclusions: By identifying the trends and costs of treatment methods used for ankle sprains and comparing WM and KM, our data provide basic information for future health policy-making. In addition, the duality of the Korean medical system is highlighted as a possible cause of increased costs.